Reconfigurable plasmonic chirality: fundamentals and applications - Neubrech, Frank; Hentschel, Mario; Liu, Na (Advanced materials, 2020)
The chiroptical response of artificial metal nanostructures can be manipulated postfabrication. Different approaches to reconfigure the chiroptical spectral signature, the structural conformation of ...